2014
DOI: 10.1007/s00167-013-2829-9
|View full text |Cite
|
Sign up to set email alerts
|

The Rotaglide mobile-bearing total knee arthroplasty: no difference between cemented and hybrid implantation

Abstract: The hypothesis that the hybrid fixation in a mobile-bearing TKA system might cause increased rate of loosening and finally failure of the arthroplasty was not confirmed. The fixation technique (cemented or hybrid) had no influence on the prosthesis's survivorship, and also on mortality rates, clinical and radiographic outcomes in a mean follow-up time of 9.5 ± 1.4 years. The Rotaglide TKA is a safe and reliable prosthesis regardless the fixation technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The difference of survival rate is not statistically significant between both types of implants, even for mobile-bearing TKA system. Iofisidis et al found that the fixation technique had no influence on the prosthesis's survivorship, and on clinical and radiographic outcomes at a mean followup of 9.5 years [28]. Their revision rate was 4.9% in the uncemented group.…”
Section: Discussionmentioning
confidence: 99%
“…The difference of survival rate is not statistically significant between both types of implants, even for mobile-bearing TKA system. Iofisidis et al found that the fixation technique had no influence on the prosthesis's survivorship, and on clinical and radiographic outcomes at a mean followup of 9.5 years [28]. Their revision rate was 4.9% in the uncemented group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, all components were cemented. In a recent study [ 17 ] on the effects of cemented versus hybrid MB TKA implantations, there were no differences found in terms of revision rates, mortality, alignment deviations or evidence of loosening, when comparing both groups. These results challenge the theoretical assumption that a hybrid fixation (cement-less femoral component) in a MB knee system might increase the rate of loosening of the femoral component.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of cementing technique on implant stability have been reported in several studies [8, 10–12, 19, 24, 29]. Stern et al [28] reported decreased micromotion by cementing the stem, and clinical studies have shown reliable long‐term survival of fully cemented stems [8, 19, 24, 29].…”
Section: Discussionmentioning
confidence: 99%